Die Bevölkerungsballung in Südost-Nigerien (Biafra) - Hoffmann-Burchardi, Helmut (ERDKUNDE, 1968)
Looking at a population map of Tropical Africa (Schmidt-Mattingly 1960 or Trewartha-Zelinsky 1953) two main regions with densities above 400 pers./sq. mile catch the eye: Nigeria and in East Africa Ruanda-Burundi and the Northeastern shores of Lake Victoria. While the concentrations of Hausa- and Yorubaland are based to a large extent on pre-colonial urbanism, a comparatively high level of political organization, indigenous crafts and trade, the extreme densities of Ruanda-Burundi (vide P. Gourou’s excellent exhaustive analytical study) and of the Ibos of Eastern Nigeria (dealt with in two recent studies by Y. Karmon and R. K. Udo) have developed under the conditions of the subsistence economy of traditional African hoe culture and the system of bush fallow. To explain them not only environment, but socio-cultural, economic, political, historical, i. e. structural reasons must be discussed (Gourou’s method; vide the rational, non-ideological school of structuralism of the French anthropologist Claude Levi-Strauss as antithesis to Sartre’s existentialism). In Ibo country, where densities rise in parts up to 800-1000 pers./sq. mile, the highest concentrations are found on the sandy Coastal Plains below 600 ft. with poor soils covered by Oil Palm Bush (Tropical Rain Forest modified by man). Historical settlement followed the lines of least resistance, i. e. easiest bush clearing, particularly on the interfluvial level hill tops, whereas the river lowlands with heavy clay soils (the Niger-Delta as well) are avoided, thus counting for a very uneven distribution of population throughout Eastern Nigeria. The Ibos are organized in localized patrilineages (extended families; maximal and minimal lineages according to G. I. Jones), living in small hamlets of 6-20 com pounds of up to 200 inhabitants. Several hamlets form, by crossing bush paths, a village group of up to 1000 persons, some of which justify by their spatial extent and continuous building coverage the term town or nucleated settlement (Onitsha Inland Town, Owerri). Their system of government is extremely democratic and egalitarian without acknowledging any supreme authority, not easily understood by British colonial Government. The town ships along the railroad (Port Harcourt, Aba, Umuahia, Enugu) were planned about 1913 by British engineers with spacious Government Reserved Areas and native quarters on a grid-iron pattern with defined building rules. High population densities have led to a largescale migration of Ibos from country to the towns (Sons Abroad) of the East, West and North (before the pogroms of 1966 and remigration to the East). The Ibos supply many new services, work(ed) as craftsmen, traders, clerks, drivers, doing any kind of business and small private enterprise (vide Indians in East Africa, Chinese traders in the Far East). They are very westernized (though at the same time very traditional in their family obligations), dynamic, clever, efficient, enterprising, adaptable, pushful etc., the most mobile (intellectually and geographically) of Nigeria’s peoples, opportunists and materialists (christianized as well), striving for money, social status and education, expecting and wanting change and progress, understanding the European concept of work. Their social psychology contrasts sharply with the feudal, reactionary Islamic structure of the Fulani and Hausa of the North, that has been reinforced by Lord Lugard’s concept of Indirect Rule, and to a lesser degree with Yoruba mentality of the West (Emirs and Obas as natural rulers); these structural and tribal differences exploded at last, smouldering since long below the surface, in the severe political crises of 1965/66 and the civil war of 1967/68.